Gamification in teaching vocabulary to secondary school students - Baratova Mohiniso (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This paper focus on exploring the effectiveness of gamification in teaching vocabulary to secondary school students. Vocabulary is considered as a fundamental component of learning languages, yet traditional learning methods cannot attract the attention of students and sustain their attention. In recent years, gamification which involves applying game-like features such as competation and rewards in non-gaming settings, has become a modern and effective method for increasing student ingagement and improving learning results. The main of this work is to investigate how stratigies of gamification affects to students’ motivation, retention and classroom participation. In this research employs both quantitive and qualitative methods, observations of classroom, test in order to check the improvement of vocabulary. Participants of secondary school students were chosen who participated in gamified vocabulary activities. The result gives the gamification is the best way to increase students' motivation to learn and memorize vocabulary easily, and to participate the lessons well. So gamified teaching gives healthy competition, collaboration among students. According to research, gamification is the best solution to teach and learn languages in both teachers and students. In can give best pedagogical tool for sides. It is recommended that If teachers use like these tools in secondary schools, they can create more convenient conditions and interactive learning environment.